ANALISIS DESKRIPTIF KETERAMPILAN TEKNIK BERMAIN SHOOTING FUTSAL PUTRI TIMNAS INDONESIA PADA KEJUARAAN AFC WOMEN’S FUTSAL ASIAN CUP CHINA 2025 - Elza Arief Fadhillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the percentage of basic shooting skills of the Indonesian Women's Futsal National Team players in the Group C preliminary round of the 2025 AFC Women's Futsal Asian Cup China. The approach used is descriptive quantitative with data sources in the form of video replays of three matches against Japan, Thailand, and Bahrain uploaded on the official AFC channel. The study population consists of all players on the Women's National Team (n = 15); data collection was conducted through video observation (counting and recording shot types) and then converted into percentages for each shooting aspect (e.g., on target, off target, player blocks, shooting area). The overall average shooting percentage for the Indonesian women's national team players was 5.64%, and the overall average match percentage was 5.45%. Against Japan, there was an improvement in performance; against Thailand, the dominant team took shots but was held to a draw (0–0); while against Bahrain, they showed high aggressiveness with a 5–1 victory. Overall, the technical shooting ability of the Women's National Team is highly proficient, but consistency in accuracy and decision-making still needs improvement to optimize the effectiveness of finishing opportunities.